raised by (1+x)
lowered by (1-x)
p - p (1+x)(1-x) = 100
100/p = 1 - [ 1-x^2]
100/p = x^2 or p =100/x^2
then
second p = 2304 = [100/x^2](1-x^2)
2304 = 100/x^2 -100
2204 = 100/x^2
22.04 = 1/x^2
x = .213
so 21.3 %
at the beginning of the year, the owner of a jewel shop raised the prices of all the jewel in his shop by x% and lowered then by x%. The price of one jewel after this up and down cycle reduced by rs 100. the owner carried out the same procedure after a month. after this second up down cycle the price of that jewel was rs 2304. find the original price of that jewel.?
Please help in easy and simplified way
3 answers
at the beginning of the year, the owner of a jewel shop raised the prices of all the jewel in his shop by x% and lowered then by x%. The price of one jewel after this up and down cycle reduced by rs 100. the owner carried out the same procedure after a month. after this second up down cycle the price of that jewel was rs 2304. find the original price of that jewel.?
But i have seen solutions which posted by your faculty but i didn't understand can you do in simplified way please help
But i have seen solutions which posted by your faculty but i didn't understand can you do in simplified way please help
If there is an easier way I do not know it.